Pengaruh Live Streaming dan Diskon terhadap Keputusan Pembelian Produk Giwigewi di Shopee - Dewasandra, Nabilah Syaharani; Artadita, Sherly (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine and analyze the influence of live streaming and discounts on purchasing decisions for Giwigewi product on Shopee. The population used in this research is all consumers who have purchased Giwigewi products via live streaming, the exact number of which is not known. The data was collected over approximately two months using a non-probability method with purposive sampling technique. A total of 100 respondents participated in filling out the questionnaires. The results of this study indicate a positive and significant influence of live streaming on the purchasing decision of Giwigewi products with a t-value of 5.022, and there is also a positive and significant influence of discounts on the purchasing decision of Giwigewi products with a t-value of 4.496. Then live streaming and discounts simultaneously have a significant effect on purchasing decisions for Giwigewi products with a fcount of 83,998. The magnitude of the influence of the live streaming and discount variables on the purchasing decision variable is 63.4%, the remaining factors not examined in this research are 36.6%.